Yoga for runners - Felstead, Christine (Human Kinetics, 2014)
Practical and accessible, this guide shows runners how to incorporate yoga into their routine to improve breathing, strength, flexibility, endurance, mental sharpness and overall athletic performance. It describes 88 poses in detail to ensure readers are able to gain the full benefit whilst at the same time decreasing the risk of injury